Causes, consequences and coping strategies of land degradation: evidence from Ethiopia - Guta Regasa Megerssa; Yadeta Bekele Bekere (Brawijaya University, 2019)
This review paper aims to review on the causes and consequences of land degradation in Ethiopia. The results from different literatures indicate that the major factors that cause land degradation in Ethiopia are: clearing woodland for agriculture , repeated cultivation, removal of residuals and dungs, single cropping, extraction of wood, , population growth, deforestation, soil erosion, low technology, inadequate extension services, political instability, cultivation on steep slopes, overgrazing, traditional way of cultivation, heavy wind, high intensity of rainfall, drought and landslides, absence of all-inclusive land use and lack of land use plans developed. On the other hand, the depletion of forests and vegetation, loss in water resources, decrease in the quality and quantity of livestock, enhancing the unemployment rate and out-migration, conflict between pastoralists, food insecurity, deceasing of soil fertility and arable land, reduction of agricultural productivity, increasing price of farm inputs, reduction of plants grown, depletion of aquifers, loss of biodiversity, reduction of potable water, shortages of timber, climate change and desertification are the major consequences of land degradation in Ethiopia. Afforestation, Reforestation, terracing, crop rotation, mixed cropping, irrigation schemes and traditional soil conservations are among the coping strategies that Ethiopian farmers are using. To overcome this problem, strengthening the teamwork among policy makers, GOs/NGOs, local communities, research institutes and the mass media are the key agents that must take these responsibilities.